The Contribution of Educational Philosophy in Improving the Quality of Learning at UPT SD Negeri 113 Inpres Laikang Elementary School, Takalar Regency - Wahyuni Wahyuni; Abdullah Sinring; Syamsu A. Kamaruddin; Ibadurrahman Ibadurrahman (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to analyze the relationship between educational philosophy and learning quality at UPT SD Negeri 113 Inpres Laikang elementary school through the application of various schools of thought such as progressivism, constructivism, and reconstructionism. The research method used a qualitative approach with a case study design, involving classroom observation, in-depth interviews with teachers, and analysis of learning documents. The results show that the consistent application of educational philosophy encourages increased student engagement, strengthens teacher-student interaction, and enriches learning experiences through student-centered activities. The constructivism approach has been shown to have the most significant impact on student learning outcomes, as evidenced by increased motivation, critical thinking skills, and collaboration. However, the study also identified several challenges, including limitations in teacher training in understanding the basic concepts of educational philosophy and difficulties in integrating it into the curriculum. This study suggests the need to strengthen teachers' pedagogical competencies through continuous training and the development of more applicable educational philosophy-based learning models.